The psychological impact of COVID-19 pandemic on the general population of Saudi Arabia - Alkhamees, Abdulmajeed A. (Compr Psychiatry, 2020)
BACKGROUND: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an emerging infection causing a widely spread pandemic of Coronavirus disease 2019 (COVID-19). The current COVID-2019 pandemic is prompting fear of falling sick, dying, helplessness and stigma, urgent and timely understanding of mental health status is needed to help the community. Our investigation designed to survey the general population in Saudi Arabia to assess the degree of psychological impact during the pandemic. METHODS: During the early stage of the outbreak, we conducted an online-based survey using a snowballing sample technique. The surveys collected data about several aspects of participant sociodemographic, knowledge, concerns, psychological impact, and mental health status. We assessed the psychological impact and mental health status using the Impact of Event Scale-Revised (IES-R), and the Depression, Anxiety, and Stress Scale (DASS-21). RESULTS: Our survey recruited 1160 respondents of the general public of Saudi Arabia. Of them, 23.6% reported moderate or severe psychological impact of the outbreak, 28.3%,24%, and 22.3% reported moderate to severe depressive, anxiety, and stress symptoms, respectively. Females reported IES-R (B: 5.46, 95% CI: 3.61 to 7.31) and DASS subscales B coefficient ranged from 1.65 to 2.63, along with high-school students, working in the medical field, and poor self-reported health status was significantly associated with a high level of IES-R and DASS scales (p < .05). Experiencing breathing difficulty and dizziness showed a stronger association with higher IES-R and DASS subscales than other somatic symptoms (e.g., headache and fever);(p < .001). Respondents who practiced specific preventative measures (e.g., hand washing, social distancing) demonstrated a protective effect against stress, anxiety, and depression symptoms. Social distancing appeared to be protective on stress and anxiety subscales (B: -1.49, 95% CI: −2.79 to −0.19),(B: -1.53, 95% CI: −2.50 to −0.57),respectively; and hand hygiene on depression subscale (B: -2.43, 95% CI: −4.44 to −0.42). CONCLUSION: Throughout the early stage of the COVID-19 outbreak in Saudi Arabia, the results showed that nearly one-fourth of the sampled general population experienced moderate to severe psychological impact. Following specific precautionary measures appeared to have a protective effect on the individual's mental health. Our findings can be used to construct psychological interventions directed toward vulnerable populations and to implement public mental health strategies in the early stages of the outbreak.